Synthesis, Characterization and Antimicrobial Activity of Novel Symmetrical and Unsymmetrical Thiadiazole Derivatives as Potential Carbonic Anhydrase Inhibitor in E. Coli - Ammar H. Al-Dujaili (Journal of Global Pharma Technology, 2019)
Ten compounds of 2, 5-disubstitutedamido-1, 3, 4-thiadiazole, 3, 5-disubstituted-amido-1, 2, 4-thiadiazole and a Schiff base of 1, 3, 4-thiadiazole derivatives were synthesized. The structures were characterized by elemental analysis and different spectroscopic techniques and their biological activities were evaluated. All the synthesized compounds were screened for their antimicrobial activity against Staphylococcus aureus and Escheriochia coli, and antifungal activity against Candida albicans and a clinical isolate of Candida albicans. Most of the compounds have shown significant antibacterial and antifungal activity. When compared with the standard antimicrobial agents. The induced fit study of Schiff base derivative showed that the compound has potential inhibitory effect on bacterial β carbonic anhydrase with binding score of (-33.681 kJ/mol).Keywords: Thiadiazole; Antibactrial activity; Antifungl activity; Amid; Coli.